A q-enumeration of lozenge tilings of a hexagon with four adjacent triangles removed from the boundary. (August 2017) - Lai, Tri
Abstract: MacMahon proved a simple product formula for the generating function of plane partitions fitting in a given box. The theorem implies a q -enumeration of lozenge tilings of a semi-regular hexagon on the triangular lattice. In this paper we generalize MacMahon's classical theorem by q -enumerating lozenge tilings of a new family of hexagons with four adjacent triangles removed from their boundary.